Critical literacy: contributions of Paulo Freire and of the new literacy studies - Alencar Nunes Macedo, Maria do Socorro (2020)
This essay aims to reflect on literacy by the articulation of two epistemological perspectives that can greatly contribute to educational research, to the formulation of public education policies and to the classroom practice. These are Paulo Freire's This essay aims to reflect on children’s literacy by articulating two epistemological perspectives: Paulo Freire's conception of education and literacy and the theory of new literacy studies (NLS), circulating in Brazil since the 1990’s. Seeking to answer to the questions “What literacy do we aim for children? What is the meaning of today’s literacy?”, our discussions indicate that a possible change in the literacy practices would go through a transformation of the writing that circulates in the school combined with a questioning pedagogy and dialog as founding principles of literacy practice.